PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN APRI COLLECTION DI KABUPATEN SUKOHARJO - Isti Mayasari; Puspita Puji Rahayu (Applied Research in Management and Business, 2022)
Employee performance is important in the production process of a company. With good performance, it can produce quality products, the number of products according to the target, high sales and huge profits for the company. Company and management have a big hand in increasing their work performance by actualizing job satisfaction for employees. Employee job satisfaction can be realized through leadership style and motivation which is met with their employee. This study aims to determine the influence of leadership style and work motivation on the performance of APRI Collection employees in Sukoharjo Regency. The population of this study was all 61 employees who were for the sample taken 60 people because the leaders were excluded from data collection so that the data was not biased. The analysis technique used multiple regression with the help of SPSS to calculate it. The results showed that leadership style and motivation had a positive and significant effect on the performance of APRI Collection employees in Kabupaten Sukoharjo.